JAMUR ARBUSKULA PADA BAMBU DIJAWA - Kartini Kramadibrata; Hadi Prastyo; Agustin Widya Gunawan (Research Center for Biology-Indonesian Institute of Sciences, 2007)
An attempt to produce arbuscular fungi (AF) spore in pot culture from bamboo soil samples collected from Meru Betiri National Park, Jember, East Java and Purwakarta, West Java was carried out by used of Pueraria phaseoloides as a host plant. The result showed nine species of AF i.e. Acaulospora foveata associated with Dendrocalamus asper and Gigantochloa apus, A. scrobiculata associated with D. asper and G. apus, A. tuberculata associated with Bambusa vulgaris, D. asper, Schizostachyum zollingeri, G.manggong and G. apus. Glotnus etunicatum associated with B. vulgaris, D. asper, G. manggong and G. apus while G. fuegianum associated with B. vulgaris, D. asper, S. zollingeri, Glomus cf. formosanum and G. geosporum, associated with D. asper and G. apus. G. mosseae associated with S. zollingeri and G. apus and Scutellospora calospora associated with G. manggong.The association of some species of AF with several species of bamboo in Java found in this study is apparently new record.